Chemopreventive Potential of Synergy1 and Soybean in Reducing Azoxymethane-Induced Aberrant Crypt Foci in Fisher 344 Male Rats - Gourineni, V. P. (Hindawi Publishing Corporation, 2011)
Synergy1, a prebiotic composed of Inulin and Oligofructose (1 : 1). Soybean meal is a natural source of isoflavones. The objective was to investigate the effects of feeding Synergy1 and SM on the incidence of azoxymethane- (AOM-) induced aberrant crypt foci (ACF) in Fisher 344 male rats. Rats (54) were randomly assigned to 9 groups (n = 6). Control group (C) was fed AIN-93G and treatment groups Syn1 and SM at 5% and 10% singly and in combinations. Rats were injected with two s/c injections of AOM at 7 and 8 weeks of age at 16 mg/kg body weight and killed at 17 weeks by CO(2) asphyxiation. Colonic ACF enumeration and hepatic enzyme activities were measured. Reductions (%) in total ACF among treatment groups fed combinations were higher (67–77) compared to groups fed singly (52–64). Synergistic mechanisms among phytochemicals may be responsible suggesting protective role in colon carcinogenesis with implications in food product development.